Comunidades evangélicas haitianas: um estudo etnográfico em Guaianases, SP - Marcelino, Bernadete Alves de Medeiros (2021)
The Haitian migration process to Brazil has raised the need for numerous researches, including its relationship with religion. In view of this scenario, this work aims to analyze the role played by Haitian evangelical communities among their supporters in migratory context in Brazil. As methodological resource, we chose ethnographic research among Haitians in the neighborhood of Guaianases, São Paulo city, in addition to bibliographic survey and open interviews. The results showed us that Haitian evangelical communities play the role of facilitators in the migratory context of their adherents, triggering a process that stimulates and drives the migration of evangelical Haitians to Brazil. We conclude that these communities become an extension of the migratory sosiale network, the understanding of this scenario can bring contributions to other research with similar themes